2008
DOI: 10.1007/s00592-008-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pioglitazone and rosiglitazone on mediators of endothelial dysfunction, markers of angiogenesis and inflammatory cytokines in type-2 diabetes

Abstract: The purpose of this study was to assess the effects of PPAR-gamma agonists (pioglitazone and rosiglitazone) on mediators of endothelial dysfunction and markers of angiogenesis in patients with type-2 diabetes. Pioglitazone group showed favorable reductions in serum total cholesterol, triglycerides, LDL cholesterol, VLDL cholesterol and increase in HDL cholesterol as compared to rosiglitazone group, after 16 weeks of treatment and also with control group. There was significant reduction of CRP level in pioglita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 33 publications
3
40
1
1
Order By: Relevance
“…Recently, CRP was reported to be independently associated with short-term mortality risk in type 2 diabetes mellitus patients [19]; and several studies have shown that pioglitazone reduces plasma CRP levels [3][4][5][6][7][8][9][10][11][12][13]. Moreover, 16 weeks of pioglitazone treatment decreased CRP levels by 42% in type 2 diabetes mellitus patients [12]; and pioglitazone further reduced CRP in patients with hypertension and diabetes who were receiving angiotensin II receptor blockers [5]. In a 6-month randomized double blind study, pioglitazone in combination with insulin treatment was shown to decrease hsCRP levels more than did insulin monotherapy alone [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CRP was reported to be independently associated with short-term mortality risk in type 2 diabetes mellitus patients [19]; and several studies have shown that pioglitazone reduces plasma CRP levels [3][4][5][6][7][8][9][10][11][12][13]. Moreover, 16 weeks of pioglitazone treatment decreased CRP levels by 42% in type 2 diabetes mellitus patients [12]; and pioglitazone further reduced CRP in patients with hypertension and diabetes who were receiving angiotensin II receptor blockers [5]. In a 6-month randomized double blind study, pioglitazone in combination with insulin treatment was shown to decrease hsCRP levels more than did insulin monotherapy alone [9].…”
Section: Discussionmentioning
confidence: 99%
“…reduction of proinflammatory markers including C-reactive protein (CRP) [3][4][5][6][7][8][9][10][11][12][13]. C-reactive protein is an acute-phase reactant that is known as a proinflammatory marker and a predictor of cardiovascular events [14][15][16].…”
mentioning
confidence: 99%
“…Pioglitazone treatment has been shown to increase serum VEGF, IL-8, and angiogenin levels in patients with type 2 diabetes. 51 In another study thiozolidinedione use in patients with type 2 diabetes was associated with diabetic macular edema.…”
Section: Studies Supporting Proangiogenic Role Of Ppar-γmentioning
confidence: 97%
“…They also reduce many other cardiovascular risk factors including: incident diabetes [2,3]; insulin resistance [4,5]; blood pressure [6]; albuminuria [7]; renal disease [8,9]; inflammatory markers [10]; revascularisation after percutaneous coronary intervention [11]; and carotid [3,[12][13][14] and coronary atherosclerosis [15,16]. These observations and analyses of data from administrative databases in 2005 show that people prescribed TZDs may have fewer cardiovascular events or deaths than people prescribed other agents [17,18] and suggest that TZDs may improve cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%